Eradication of post‐lobectomy mucormycosis and bacterial empyema with intrapleural antimicrobial therapy in a patient with surgically resected Mycobacterium xenopi (non‐tuberculous Mycobacteria) pulmonary infection. Issue 4 (8th March 2023) - Wigston, Charlotte; Woolnough, Emily; Otome, Ohide; Sanders, Lucas; Fysh, Edward
Abstract: Empyema thoracis is a collection of pus in the pleural space associated with pleural fibrin deposition. Treatment involves systemic antimicrobials, pleural drainage, intrapleural enzymes and sometimes decortication. Our case is a 57‐year‐old gentleman who developed chronic mucormycosis ( Cunninghamella sp. ) and bacterial ( Enterococcus sp .) empyema in a high‐risk post‐lobectomy space in the setting of a non‐expandable lung following non‐tuberculous mycobacterial (NTM) infection. The patient did not tolerate antimicrobial therapy for progressive pulmonary NTM infection, and required lobectomy, complicated by polymicrobial empyema. He did not respond to systemic treatment and long‐term intercostal catheter drainage and therefore intrapleural taurolidine‐citrate, and enzyme therapy was used to help eradicate infection. Intrapleural antifungals and taurolidine‐citrate in combination with long‐term antifungal therapy may help eradicate infection in patients with fungal empyemas. Further studies investigating the safety of taurolidine‐citrate in pleural catheters are needed. Abstract : We present a 57‐year‐old gentleman who developed chronic mucormycosis ( Cunninghamella sp.) and bacterial ( Enterococcus sp.) empyema in a high‐risk post‐lobectomy space in the setting of a non‐expandable lung following non‐tuberculous mycobacterial infection. This was successfully treated with a combination of systemic and intrapleural therapies.